DRIVERS OF FIRM VALUE IN INDONESIA’S FOOD AND BEVERAGE SECTOR: THE ROLE OF CAPITAL STRUCTURE AND INTELLECTUAL CAPITAL - Izza Ashsifa; Muhammad Teguh Kuncoro (TECHNOBIZ : International Journal of Business, 2025)
This study aims to examine the influence of capital structure and intellectual capital on firm value, with firm size and firm growth as moderating variables. Focusing on food and beverage companies listed in Indonesia, the study analyzes 66 firms using multiple regression analysis. The findings reveal that both capital structure and intellectual capital have a significant positive impact on firm value. Furthermore, firm size significantly moderates these relationships, weakening the influence of both capital structure and intellectual capital as firms become larger. However, firm growth does not show a significant moderating effect. These results underscore the importance of aligning financial and intellectual strategies with firm-specific characteristics to maximize value creation. This research contributes to the literature by integrating financial and intangible resource perspectives, offering insights for managers and investors in optimizing strategic decisions in the food and beverage sector.